Situation in corrective labor camps of Molotov Oblast in the postwar decade (based on the materials of the public prosecutor’s supervision) - Oleg L. Leibovich (Historia provinciae: журнал региональной истории, 2022)
The article presents the results of a study of the social crisis in the Gulag during the first postwar decade. The study focuses on the camps and colonies located in Molotov Oblast. The main sources of the study are the materials of prosecutor’s supervision that are stored in the corresponding fonds of the State Archive of Perm Krai and the Perm State Archive of Socio-Political History. Special attention is paid to the activities of D. Kulyapin, Public Prosecutor of the oblast (1942–49). Studying the literature on the subject made it possible to formulate an explanatory model, according to which the Gulag crisis includes several components: economic, social, and cultural ones. It is associated with increasing social tensions in the postwar Soviet society: the conflict of particularistic interests of different social communities, the growth of internal and external aggressiveness, and other features of social disorganization. One of the manifestations of social disorganization is the aggravation of interdepartmental conflicts, including those between various punitive institutions. The prosecutor’s office was put in such a position that its employees had to defend its constitutional status, which was in fact challenged by the bodies of the MGB and the MVD. For this reason, prosecutor’s supervision was aimed at revealing shortcomings, violations, and lawlessness at the regional levels of the camp system. D. Kulyapin formulated the main features of the “unsatisfactory state of affairs” in the camps: administrative arbitrariness and excessive exploitation of forced labor resulting in physical exhaustion and mortality of prisoners and also, in extreme cases, riots in the colonies. He saw the causes of what was happening in the ignorance of the camp staff, their lack of humanity or, in other words, the low level of their general and professional culture on the one hand, and on the other hand – in the introduction of self-sufficiency in the camp economy, which entailed economizing on food supplies, hygiene and care products, etc. for the prisoners. The prosecutor offered to remedy the situation in the camps by means of educating the camp staff about socialist morality, exemplary punishment of the guilty, and strengthening of supervision measures, i.e. essentially habitual and inefficient methods of the Soviet penitentiary system. Nevertheless, D. Kulyapin’s reports diagnosed the state of affairs in the postwar Gulag quite adequately.